2008
DOI: 10.1002/ajmg.b.30704
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐O‐methyltransferase Val158Met polymorphism is associated with methylphenidate response in ADHD children

Abstract: Methylphenidate is the most frequently prescribed drug in the treatment of attention deficit hyperactivity disorder (ADHD) but it is not effective in every case. Therefore, identifying genetic and/or biological markers predicting drug-response is increasingly important. Here we present a case-control study and pharmacogenetic association analyses in ADHD investigating three dopaminergic polymorphisms. Previous studies suggested variable number of tandem repeats (VNTR) in the dopamine D4 receptor (DRD4) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 34 publications
8
61
1
3
Order By: Relevance
“…Numerous studies have investigated the relationship between the Val158Met polymorphism and behavioral phenotypes and various psychiatric disorders. The COMT Val158Met genotype has been reported as a risk factor for schizophrenia, bipolar disorder, obsessive-compulsive disorder, aggressive behavior, and attention problems, although some studies conclude the opposite (Eisenberg et al, 1999;Kereszturi et al, 2008;Sengupta et al, 2008). The functional COMT Val158Met polymorphism has been thoroughly investigated in several psychiatric disorders (Craddock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have investigated the relationship between the Val158Met polymorphism and behavioral phenotypes and various psychiatric disorders. The COMT Val158Met genotype has been reported as a risk factor for schizophrenia, bipolar disorder, obsessive-compulsive disorder, aggressive behavior, and attention problems, although some studies conclude the opposite (Eisenberg et al, 1999;Kereszturi et al, 2008;Sengupta et al, 2008). The functional COMT Val158Met polymorphism has been thoroughly investigated in several psychiatric disorders (Craddock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have revealed associations between the Val allele and forms of distractibility and "off-task" behavior (Sengupta et al, 2008;Holmboe et al, 2010). Others have reported an association between the Val allele and ADHD (Eisenberg et al, 1999;Kereszturi et al, 2008). Some groups, have found associations between the Met allele and increased ADHD symptom count or severity in young subjects (DeYoung et al, 2010;Palmason et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usually prescribed psychostimulant is methylphenidate (MPH) that presents an estimated 70% response rate in ADHD affected children (Elia et al, 1991;Spencer et al, 1996). According to pharmacogenetic studies, the inter-individual differences in stimulantresponse may be related to genetic influences (Kirley et al, 2003;Langley et al, 2005;Gilbert et al, 2006;Winsberg & Comings, 1999;Roman et al, 2002;Purper-Ouakil, 2008;Kereszturi et al, 2008;da Silva et al, 2008) and the search for candidate genes associated with ADHD focused on the catecholamine system. Genes associated with increased risk for ADHD are the dopamine transporter (DAT1) (Purper-Ouakil, 2008), the dopamine receptors (DRD4 and DRD5) (Van Tol et al, 1992), serotonin transporter (5-HTT), and synaptosomalassociated protein (SNAP-25) (Husain et al, 2007;Faraone et al, 2005;McGough et al, 2006).…”
Section: Pharmacogenomics Tools In the Paediatric Populations: State mentioning
confidence: 99%
“…Genes associated with increased risk for ADHD are the dopamine transporter (DAT1) (Purper-Ouakil, 2008), the dopamine receptors (DRD4 and DRD5) (Van Tol et al, 1992), serotonin transporter (5-HTT), and synaptosomalassociated protein (SNAP-25) (Husain et al, 2007;Faraone et al, 2005;McGough et al, 2006). Other genes of potential interest in pharmacogenetic studies include catehol-O-methyltransferase (COMT) (Kereszturi et al, 2008 ), the adrenergic 2-receptor (ADRA2A and ADRA1A) (da Silva et al, 2008;Polankzyk et al, 2007;Elia et al, 2009) (Fig. 2).…”
Section: Pharmacogenomics Tools In the Paediatric Populations: State mentioning
confidence: 99%